Development and optimization of zeolite synthesis route from natural koalin for adsorption of dyes - Abdullahi, Tijjani (2019)
Synthesis of zeolite using kaolin as the main source of alumina and silica has been identified as a novel zeolite production process, which could reduce the cost of using the synthetic reagents and the high energy consumption. A low grade kaolin was used for studying the most suitable synthesis route and operating parameters for producing a high yield and pure phase zeolite. The study adopted the alkaline activation and microwave assisted heating as modification techniques of the conventional hydrothermal synthesis process. Calcination and crystallization proceses were identified as the bottleneck operations within the process. Hence, this study employed 2k factorial design of experiment to study the relationship of metakaolinization temperature of 600 – 800 oC with calcination time of 1 – 5 hours. And that of crystallization time of 9 – 16 hours with aging treatment time of 12 – 36 hours. Central Composite Design (CCD) is used for optimization with axial and center point for factors evaluation towards the responses; yield percent (%) and crystallinity (%) for crystallization process. Based on the Response Surface Methodology (RSM), with desirability value of 98.67 %, the significant parametric aging condition is 27 hours and crystallization time is 9 hours were suggested to yield an optimum product for 80.47 yield percent and 76.92 crystallinity. Three confirmation runs were performed based on the suggested optimum parameter and the calculated error value was found to be below 10 %. The synthesized zeolite-A from the confirmation runs was characterized through XRD. The results were then corroborated with the analytical results from SEM, BET and FTIR. The activity of the synthesized zeolite A was confirmed by a structural refinement analysis, that identified the product as a member of the cubic crystalline systems, belonging to a Fm3c space group with lattice cubic structure values where: